THE USE OF IMPORTANCE-PERFORMANCE ANALYSIS (IPA) IN EVALUATING FACTORS INFLUENCING DATA QUALITY OF PUBLIC SECTOR ACCOUNTING INFORMATION SYSTEM IN INDONESIA - Muliyani, Muliyani (Accounting and Business Journal, 2020)
The focus of this paper is to evaluate the critical factors influencing data quality of accounting information system in public sector of Indonesia. In this reseach, the Importance-Performance Analysis (IPA) grid was used to measure the critical factors from the informatin producer’s perspective. A list of 23 influencing factors was identified from prevous studies and each of the factors was rated using a five point Likert scale. On a five point Likert scale, the survey enables respondent to rate the relative importance of the factors, followed by another factor’s performance rating. The purpose of the survey is not only to measure the actual satisfaction level, but also to highlights important areas to improvements. The IPA, a two dimensional grid, is broken into four categories: (1) concentrate Here; (2) Keep Up the Good Work; (3) Low Priority; and (4) Possible Overkill, to enable each of the factors to be plotted in to the grid. It is clear and powerful evaluation tool for organisation to find out factors that are going well and factors that need to be improved, which require action immediately. The results are useful in identifying areas for strategic focus to help develop the quality of information generated by the information system.